SA1/SA2 cohesion proteins and SIRT1-NAD+ deacetylase modulate telomere homeostasis in cumulus cells and are eligible biomarkers of ovarian aging. Issue 5 (22nd February 2018) - Valerio, D; Luddi, A; De Leo, V; Labella, D; Longobardi, S; Piomboni, P
Abstract: STUDY QUESTION: Are cohesins SA1/SA2 and the NAD-dependent deacetylase SIRT1 involved in telomere homeostasis of cumulus cells and thus eligible as biomarkers of follicular physiology and ovarian aging? SUMMARY ANSWER: SA1/SA2 cohesins and SIRT1 are associated with telomere length in cumulus cells and may be eligible biomarkers of follicular physiology and ovarian aging. WHAT IS KNOWN ALREADY: In somatic cells, cohesins SA1/SA2 mediate sister chromatid cohesion at the telomere termini (for SA1) and along chromatid arms (for SA2). The NAD + -dependent protein deacetylase Sirtuin 1 (SIRT1), which preserves DNA integrity from oxidative stress, may also modulate genome stability and telomere length. STUDY DESIGN, SIZE, DURATION: Collectively 280 cumulus/oocyte complex samples were recovered from a total of 50 women undergoing in vitro fertilization. PARTICIPANTS/MATERIALS, SETTING, METHODS: Cumulus cells were separated from the oocyte–cumulus complex. DNA and total mRNA were extracted from cumulus cells and assayed for telomere length and for SA1, SA2 and SIRT1 gene expression profiling. Telomere length was determined by quantitave PCR and analyzed relative to the single copy of the housekeeping gene (albumin) to generate a T/S ratio (Telomere/single copy gene). Gene expression levels of SA1, SA2 and SIRT1 mRNA were assayed by quantitative RT-PCR and confirmed by western blotting and immunofluorescent studies (SIRT1). SA1/SA2 and SIRT1 gene expression levels and telomere length analysis of patients/samples were ranked in relation to their clinical setting parameters (BMI, age) and to the number of oocyte retrieved. MAIN RESULTS AND THE ROLE OF CHANCE: SA1 and SA2 transcripts were both detected in all cumulus cells analyzed and the relative amount showed a clear decreasing trend according to the age of patients. A significant increase in SA1 and SA2 was disclosed in high responder women (>6 oocytes retrieved) compared to poor responders (<4 oocytes) ( P < 0.05). Furthermore, statistically significant positive correlations were also recorded between the transcripts levels of the two cohesin molecules ( r = 0.89; P < 0.05) and, to a lesser extent, between telomere length and SA1 ( r = 0.42; P < 0.001) and SA2 ( r = 0.36; P < 0.001) mRNA levels. SIRT1 expression was also significantly increased in high responders (>6 oocytes) compared to poor responders. Significant correlations were found between SIRT1 and SA1 ( r = 0.69; P < 0.001), between SIRT1 and SA2 ( r = 0.78; P < 0.001), and between SIRT1 and telomere length ( r = 0.36; P < 0.001). However, in the older patient group (>38 years), SIRT1 mRNA levels were twice as high as the levels recorded in the younger patient cohort (<34 years). Western blot analysis and immunofluorescent studies confirmed the increments in SIRT1 protein levels in patients over 38 years old. LARGE SCALE DATA: N/A. LIMITATIONS, REASONS FOR CAUTION: Cumulus/oocyte complexes were retrieved by patients undergoing ovarian stimulation protocol for IVF. We cannot exclude the possibility that different stimulation protocols affect the correlations highlighted in this study. Future investigations should shed light on cumulus cells molecular profile according to different stimulation protocols. WIDER IMPLICATIONS OF THE FINDINGS: The overall results of our study point to the involvement of cohesins SA1/SA2 and SIRT1 deacetylase in telomere homeostasis in cumulus cells and highlight their possible eligibility as biomarkers of follicular physiology and ovarian aging. STUDY FUNDING/COMPETING INTEREST(S): Merck Serono S.P.A Italy sponsored the study with financial support. There are no competing interests to declare.